Pengaruh Pemotongan Gaji terhadap Tapera (Tabungan Perumahan Rakyat) pada Mahasiswa Kelas Karyawan di Universitas Bina Sarana Informatika - Debi Anggraeni; Justian Megi; Melati Miftahul Janah; Nadilla Dwi Karunia; Shinta Tamira (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This research aims to analyze the effect of salary cuts for Public Housing Savings (Tapera) on the economic conditions and learning motivation of employee class students at Bina Sarana Informatika University (UBSI). Using a quantitative approach with survey methods, data was collected from 150 respondents who were employee class students at UBSI. The research results show that salary cuts for Tapera have a significant influence on students' economic conditions, but do not significantly influence their learning motivation.